Fundamentals of motor behavior - Fairbrother, Jeffrey T. 1964- (Fundamentals of sport and exercise science series, 2010)
Provides an overview of the field of motor behaviour. This book introduces the reader to the field: how it emerged, the questions that interest people in the field, how they go about trying to answer those questions and potential career options. It also includes an epilogue that asks a series of 'what will you do?' questions